KONTRIBUSI STATUS ERGONOMI TERHADAP KETERBATASAN FUNGSIONAL NECK PADA ESPORTS PLAYER - Muttaqqin, Zaenal; Rahman, Farid (Poltekkes Kemenkes Bandung, 2025)
According to the data, esports players tend to spend long hours in a sitting position while playing or training for competitions. Several studies have shown that esports players engage in sedentary behavior for 4.2 hours daily during training. This condition is certainly worrying because someone who sits for too long and without paying attention to ergonomic status will be able to trigger fatigue and even injury. This study aimed to determine whether or not ergonomic status contributes to functional neck limitations in esports players. This research was a cross-sectional study with 284 esports player respondents obtained through purposive sampling technique with the calculation of the lemeshow method. The research was conducted from January - March 2024 through a virtual form platform. This study used Rapid Upper Limb Assessment (RULA) and Neck Disability Index (NDI) measuring instruments. Data analysis was conducted using the Spearman correlation and binary regression logistic tests. The Spearman correlation test analysis results showed a value of (p-value 0.713 > 0.05). Binary Regression Test Analysis found the value (p-value 0.608 > 0.05). It was found that ergonomic status has no contribution or influence on functional neck limitations in esports players.